Boundedly rational consumers, energy and investment literacy, and the display of information on household appliances - Julia Blasch; Massimo Filippini; Nilkanth Kumar (ETH Zurich, CER-ETH - Center of Economic Research, 2016)
It is an ongoing debate how to increase the adoption of energy-efficient light bulbs and household appliances in the presence of the so-called 'energy efficiency gap'. One measure to support consumers' decision-making towards the purchase of more efficient appliances is the display of energy-related information in the form of energy-efficiency labels on electric consumer products. Another measure is to educate the consumers in order to increase their level of energy and investment literacy. Thus, two questions arise when it comes to the display of energy-related information on appliances: (1) What kind of information should be displayed to enable consumers to make rational and efficient choices? (2) What abilities and prior knowledge do consumers need to have to be able to process this information? In this paper, using a series of recursive bivariate probit models and three samples of 583, 877 and 1, 375 Swiss households from three major Swiss urban areas, we show how displaying information on the future energy consumption of electrical appliances in monetary terms, i.e. as an estimate of yearly energy cost (CHF) rather than in physical units (kWh), increases the probability that an individual performs an investment analysis and hence chooses the most (cost-)efficient appliance. In addition, our econometric results suggest that individuals with a higher level of energy and, in particular, investment literacy are more likely to perform an optimization rather than relying on a decision-making heuristic and are more likely to identify the most (cost-)efficient appliance.
Keywords: D12; D80; Q41; Q48; 330; energy-efficiency; bounded rationality; energy-using durables; information; energy label; energy literacy; choice experiment; Energieeinsparung; Lampe; Umweltzeichen; Konsumentenverhalten; Begrenzte Rationalität; Probit-Modell; Ballungsraum; Schweiz